Risk factors and quality of life in urinary incontinence females in the Care and Medical Centre in Kielce - Dutkiewicz, Sławomir; Kapusta, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2011)
Introduction: Urinary incontinence is one of ten most significant socio-medical problems. This particular disease occurs more often in females. It affects about 3 million females in Poland yearly. Aim of the study: The aim of the study is to assess risk factors and quality of life in urinary incontinence female patients at the Care and Medical Centre in Kielce (Zakład Opiekuńczo Leczniczy w Kielcach). Material and methods : 60 females aged 50 and more with a different degree of urinary incontinence were involved in the study. Results: Study 60 (100%) women with urinary incontinence also had hypertension and dysfunction of circulatory, respiratory and movement systems while in 46 (77%) women chronic diseases, i.e. Alzheimer`s disease, diabetes, multiple sclerosis, cerebral hemorrhage, stroke were also present. It was ascertained that in study 46 females’ group no factors like: age, education, place of living or occupation made a contribution to the disease. Urinary tract infection (UTI) when recurrent is yet another risk factor for urinary incontinence. Among 60 (100%) females, statistically one may conclude (p = 0.05) that UTI symptoms were affected by age. Some types of medicines, i.e. diuretics, antidepressants or antihypertensives also contribute to the growing number of females suffering from urinary incontinence. Age and place of living affect the number of individuals taking these medications at a significance level of p = 0.05. Conclusions : The analysis resulting from the study reveals that symptoms like dysuria and urgent incontinence were more frequent in women over 70 years. Urinary incontinence turned out to be affected by a number of causes and it depends on urinary tract infections, procedures involving the crotch region, number of deliveries, some diseases and groups of medications. Urinary incontinence is a nuisance and it results in a change of quality of live.